Isoflurane preconditioning protects against ischemia-reperfusion injury partly by attenuating cytochrome c release from subsarcolemmal mitochondria in isolated rat hearts - Qian Li-ping; Zhu Shan-shan; Cao Jun-li; Zeng Yin-ming (Acta Pharmacologica Sinica; Vol 26, No 7 (July 2005): Acta Pharmacologica Sinica, 2016)
Aim: To examine if isoflurane preconditioning can attenuate ischemia/reperfusion injury by reducing cytochrome c release from inner mitochondrial membrane. Methods: Isolated hearts of Sprague-Dawley rats were perfused on Langendorff apparatus. Hearts were randomly assigned to a non-treated group (CON group, n=12) or three isoflurane preconditioning groups (0.5% ISC group, 1.0% ISC group, and 2.0% ISC group; n=12). In the latter three groups, isoflurane was given at concentrations of 0.5%, 1.0%, and 2.0% for 15 min with 15-min washout before 30-min ischemia. Subsarcolemmal mitochondria of the myocardium were isolated after 60-min reperfusion. Hemodynamics of the each heart was recorded, infarct size of the hearts and contents of cytosolic cytochrome or mitochondrial cytochrome c were measured at the end of reperfusion. Morphology of isolated mitochondria in the four groups was evaluated, respectively. Results: Compared with the CON group, cytosolic cytochrome c in 0.5% ISC group, 1.0% ISC group, and 2.0% ISC group were significantly decreased along with a significant increase of mitochondrial cytochrome c. Infarct size of the hearts in the four groups were 56%plusminus12%, 41%plusminus12%, 32%plusminus7% and 33%plusminus11%, respectively. The values of the three isoflurane preconditioning groups were significantly lower than that of the CON group (P < 0.05). Isoflurane exposure before ischemia can attenuate the change of morphology of mitochondria after reperfusion. The effects of 2.0% isoflurane on reducing cytochrome c release were more remarkable than 0.5% and 1.0% concentrations of isoflurane. Conclusion: Myocardioprotective effects of isoflurane preconditioning were associated with attenuation of cytochrome c loss from the inner membrane of subsarcolemmal mitochondria.